<span><span><span>1/2</span><span>(<span><span>2g</span>−3</span>)</span></span>=<span>−<span>4<span>(<span>g+1</span>)</span></span></span></span>
<span><span><span>1/2</span><span>(<span><span>2g</span>−3</span>)</span></span>=<span>−<span>4<span>(<span>g+1</span>)</span></span></span></span>
<span><span>g+<span><span>−3/</span>2</span></span>=<span><span>−<span>4g</span></span>−4</span></span>
<span><span><span>g+<span><span>−3/</span>2</span></span>+<span>4g</span></span>=<span><span><span>−<span>4g</span></span>−4</span>+<span>4g</span></span></span><span><span><span>5g</span>+<span><span>−3</span>2</span></span>=<span>−4</span></span>
5g+−3/2+3/2=−4+3/2
<span><span>
5g</span>=<span><span>−5/</span>2</span></span>
<span><span><span>5g/</span>5</span>=<span><span><span>−5</span>2</span>5</span></span><span>
g=<span><span>−1</span><span>2
Hoped I helped!</span></span></span>
Answer:
Step-by-step explanation:
from the graph of f(x)
when x=1,f(x)=0
or f(1)=0
when f(x)=2,x=2
for g(x)
when x=6,g(x)=16
or g(6)=16
when g(x)=18,x=32
for h(x)
when x=14
h(x)=27x-7
h(14)=27×14-7=7(27×2-1)=7(54-1)=7×53=371
h(x)=-493
27x-7=-493
27 x=-493+7=-486
3 x=-54
x=-18
for p(t)
when t=94
p(t)=24
p(94)=24
p(t)=67
t=31
Answer:
Step-by-step explanation:
<u>Given equation:</u>
The left side is absolute value, we know it is zero or positive value but never negative.
The right side is negative so the equation can't have solutions as we have contradiction above.